PENGARUH KARAKTERISTIK DAERAH DAN OPINI AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Salfadhilah, Alma; Sumardjo, M.; Wijaya, S.Y. (Jurnal Akunida, 2021)
This research aims to analyze the effect of regional wealth, regional depend, total assets, and audit opinion. In this research, the population is the district/city on Kalimantan Island during the priode 2015 to 2019. This research used the Purposive Sampling and testing the hypothesis was through multiple linear regression using SPSS. The test results obtained that the regional wealth negatively significant, regional depend did not significant affect, total assets has a significant positif, and audit opinion has a significant positive on the level of LKPD disclosure.